Saturating stiffness control of robot manipulators with bounded inputs - Rodríguez-Linán, María del Carmen; Mendoza, Marco; Bonilla, Isela; Chávez-Olivares, César (Zielona Góra: Uniwersytet Zielonogórski)
A saturating stiffness control scheme for robot manipulators with bounded torque inputs is proposed. The control law is assumed to be a PD-type controller, and the corresponding Lyapunov stability analysis of the closed-loop equilibrium point is presented. The interaction between the robot manipulator and the environment is modeled as spring-like contact forces. The proper behavior of the closed-loop system is validated using a three degree-of-freedom robotic arm.
Keywords: bounded inputs; robot manipulator; saturation; stiffness control